THE RESPONDS OF DIRECTIVE SPEECH ACTS BY THE CHARACTERS IN JACK THE GIANT SLYER (2013) MOVIE - Ruminda, Ruminda (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2018)
This research presents the responds of the hearers as the effects of directive speech acts that are given by the characters in Jack the Giant Slyer (2013) movie. The research is aimed to analyze the categories of responds resulted from the addresses when they are asked to do something by using the theory about directive speech act by Leech (1983). The result of the analysis shows that the responds of the characters that are found in some categories are in the form of action responds, verbal responds, action and verbal responds and no responds. The most type of directive speech acts that is responded by the action is commanding, and the least of it is suggesting.